PENERAPAN ASUHAN KEPERAWATAN PADA PASIEN BROCHOPNEUMONIA DALAM PEMENUHAN KEBUTUHAN OKSIGENASI - ratna mahmud (Media Keperawatan:Politeknik Kesehatan Makassar, 2020)
ABSTRACT Introduction: Children are very vulnerable to various diseases which can be caused by germs, viruses and other microorganisms. Diseases that often occur in children are diseases of the respiratory tract. Oxygen is needed by the body to maintain the continuity of cell metabolism so that it can maintain life and activity of various cells, tissues or organs. Bronchopneumonia is inflammation of the lungs that affects one or several marked lung lobes marked by the presence of patches of infiltrate caused by bacteria, viruses and fungi and foreign objects. Purpose: to describe nursing care to fulfill oxygenation needs. Method: the method used in the preparation of scientific papers is descriptive method, with a case study approach taken in Dahlia Hospital Room. TK II Pelamonia Makassar on May 28 to June 2, 2018. Data were obtained from mothers of patients and nurses. Results: after 3x24 hours of nursing action patients with bronchopneumonia complained of slimy cough and ronchi breath sounds and the client's mother's effort when handling her child's slimy cough was to provide warm water to the client. Providing interventions to assess the frequency or monitoring of breathing, Auscultation of additional breath sounds (ronchi, wheezing), provide a comfortable position such as the position of semi-fowler, wish and collaboration giving nebulizer gives changes to the ineffective airway clearance. Conclusion: Handling the ineffectiveness of airway clearance is associated with excessive secretion production by providing a semi-fowler position and nebulizer therapy has an effect on the dilution of mucus and sputum which obstruct the airway.Key words: Bronchopneumonia, Ineffective airway clearanceABSTRAKPendahuluan: Anak sangat rentang terhadap berbagai penyakityang bisa disebabkan oleh kuman, virus dan mikroorganisme lain. Penyakit yang sering terjadi pada anak yaitu penyakit pada saluran pernafasan. Oksigen dibutuhkan oleh tubuh untuk menjaga kelangsungan metabolisme sel sehingga dapat mempertahankan hidup dan aktivitas berbagai sel, jaringan atau organ.. Bronchopneumonia merupakan  radang paru-paru yang mengenai satu atau beberapa lobus paru-paru yang  ditandai yang ditandai dengan adanya bercak-bercak infiltrate yang disebabkan oleh bakteri, virus dan jamur dan benda asinng.Tujuan : untuk menggambarkan  asuhan keperawatan pemenuhan kebutuhan oksigenasi. Metode : metode yang digunakan dalam penyusunan karya tulis ilmiah ini adalah metode deksriptif, dengan pendekatan studi kasus yang diambil di Ruangan Dahlia RS. TK II Pelamonia Makassar pada tanggal 28 Mei s/d 02 Juni 2018. Data diperoleh dari ibu pasien dan perawat. Hasil : setelah dilakukan tindakan keperawatan 3x24 jam pasien dengan bronkopneumonia  mengeluhkan  batuk berlendir dan suara nafas ronchi dan usaha ibu klien saat menangani batuk berlendir anaknya adalah memberikan air hangat kepada klien .  Pemberian intervensi  mengkaji  frekuensi atau pantau pernafan, Auskultasi bunyi nafas tambahan ( ronchi,wheezing), berikan posisi yang nyaman misalnya posisi semi fowler, ingin dan kolaborasi pemberian nebulizer memberikan perubahan  pada bersihan jalan nafas tidak efektif.  Kesimpulan : Penanganan  ketidakefektifan bersihan jalan nafas berhubungan dengan produksi sekret yang berlebihan dengan memberikan posisi semi fowler dan terapi nebulizer memberi pengaruh terhadap pengenceran lendir dan sputum yang menyumbat jalan nafas.